Herpes Simplex Virus Internalization into Epithelial Cells Requires Na(+)/H(+) Exchangers and p21-Activated Kinases but neither Clathrin- nor Caveolin-Mediated Endocytosis - Devadas, Deepika (J Virol, 2014)
Herpes simplex virus 1 (HSV-1) is an alphaherpesvirus that has been reported to infect some epithelial cell types by fusion at the plasma membrane but others by endocytosis. To determine the molecular mechanisms of productive HSV-1 cell entry, we perturbed key endocytosis host factors using specific inhibitors, RNA interference (RNAi), or overexpression of dominant negative proteins and investigated their effects on HSV-1 infection in the permissive epithelial cell lines Vero, HeLa, HEp-2, and PtK(2). HSV-1 internalization required neither endosomal acidification nor clathrin- or caveolin-mediated endocytosis. In contrast, HSV-1 gene expression and internalization were significantly reduced after treatment with 5-(N-ethyl-N-isopropyl)amiloride (EIPA). EIPA blocks the activity of Na(+)/H(+) exchangers, which are plasma membrane proteins implicated in all forms of macropinocytosis. HSV-1 internalization furthermore required the function of p21-activated kinases that contribute to macropinosome formation. However, in contrast to some forms of macropinocytosis, HSV-1 did not enlist the activities of protein kinase C (PKC), tyrosine kinases, C-terminal binding protein 1, or dynamin to activate its internalization. These data suggest that HSV-1 depends on Na(+)/H(+) exchangers and p21-activated kinases either for macropinocytosis or for local actin rearrangements required for fusion at the plasma membrane or subsequent passage through the actin cortex underneath the plasma membrane. IMPORTANCE After initial replication in epithelial cells, herpes simplex viruses (HSVs) establish latent infections in neurons innervating these regions. Upon primary infection and reactivation from latency, HSVs cause many human skin and neurological diseases, particularly in immunocompromised hosts, despite the availability of effective antiviral drugs. Many viruses use macropinocytosis for virus internalization, and many host factors mediating this entry route have been identified, although the specific perturbation profiles vary for different host and viral cargo. In addition to an established entry pathway via acidic endosomes, we show here that HSV-1 internalization depended on sodium-proton exchangers at the plasma membrane and p21-activated kinases. These results suggest that HSV-1 requires a reorganization of the cortical actin cytoskeleton, either for productive cell entry via pH-independent fusion from macropinosomes or for fusion at the plasma membrane, and subsequent cytosolic passage to microtubules that mediate capsid transport to the nucleus for genome uncoating and replication.